2002
DOI: 10.1597/1545-1569(2002)039<0255:anstar>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A New Scale to Assess Radiographic Success of Secondary Alveolar Bone Grafts

Abstract: The above scale can be used to determine accurately the position of bone within the cleft site. It can be used in the mixed dentition prior to eruption of the canine. It demonstrated moderate to substantial inter- and intraobserver reliability and offers several advantages, compared with other scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 13 publications
1
64
1
13
Order By: Relevance
“…The formation rate of the bone bridge in bone grafting is measured using an index of alveolar bone height (Abyholm et al, 1981;Sindet-Petersen and Enemark, 1985;Bergland et al, 1986;Enemark et al, 1987;Kalaaji et al, 1994;Long et al, 1995;Kindelan et al, 1997;Witherow et al, 2002). Recent investigations showed that the assessment based on X-ray findings can over-or underestimate the bony bridge by 17e25%, in comparison with the results of evaluation by computed tomography (CT) (Lee et al, 1995;Rosenstein et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The formation rate of the bone bridge in bone grafting is measured using an index of alveolar bone height (Abyholm et al, 1981;Sindet-Petersen and Enemark, 1985;Bergland et al, 1986;Enemark et al, 1987;Kalaaji et al, 1994;Long et al, 1995;Kindelan et al, 1997;Witherow et al, 2002). Recent investigations showed that the assessment based on X-ray findings can over-or underestimate the bony bridge by 17e25%, in comparison with the results of evaluation by computed tomography (CT) (Lee et al, 1995;Rosenstein et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…12 The quantity of bone tissue at the cleft site post-SBG was evaluated using occlusal radiographs acquired at 3-12 months post-SBG and at T2 by means of alveolar bone graft (ABG) scores (0-4 points) assigned on the side of cleft-adjacent U1 ( Figure 3). 13 …”
Section: Evaluation Of Occlusal Radiographsmentioning
confidence: 99%
“…En sık kullanılan yöntemler; Bergland 23 , Chelsea 39 ve Kindelan 40 skalaları olarak özetlenebilir. Bergland skalasında yarık bölgesindeki kemik yüksekliği periapikal radyografiler üzerinde 4 sınıfa ayrılarak puanlanır.…”
Section: Alveoler Yarık Onarımının Başarısının Değerlendirilmesiunclassified